Prevalence of Hypertension and Associated Risk Factors among Post-Menopausal Women of Boalkhali Upazila of Chattogram District: Cross Sectional Observational Study - Chowdhury, MSI Tipu; Chowdhury, Rajsree; Sultana, Sadia; Hossain, Mohammad Akram; Sultan, Mohammad Ashraf Uddin; Abdullah, Abu Sadik; Mahmud, Sohel; Bari, Ahmed Saiful; Fatema, Nilufar; Mahbub, SM Ear E; Khaled, Md Fakhrul Islam; Ahmed, Khurshed (University Heart Journal, 2025)
Background: Prevalence of hypertension increases with age and postmenopausal women remain at higher risk than other population group. Various risk factors attribute to the precipitation of the postmenopausal hypertension, however definitive mechanism have not been completely explicated till date. Aims of the study: The study attempted to evaluate the prevalence of hypertension and associated risk factors among postmenopausal women of Boalkhali Upazila, Chattogram, Bangladesh. Materials and method: This cross-sectional study was conducted at Boalkhali Upazila of Chattogram District with total 400 post-menopausal women who have been included in this study with convenient sampling method. Results: The study results showed that, mean age of postmenopausal women was 58.65±7.67 years, 11.75% of them had pre-hypertension and 35.75% of them had hypertension. A logistic regression analysis showed that, age, marital status, menopausal onset, BMI, hip circumference, family history of comorbidities (hypertension, diabetes mellitus and both hypertension and diabetes mellitus), comorbidities of the respondents such as diabetes mellitus, ischemic heart disease and sedentary life style were independent risk factors of hypertensive status of the post-menopausal women when adjusted for other risk factors (p<0.05) Conclusion: This study conclude that, high prevalence of hypertension among post-menopausal women. So, its need to be more concern about post-menopausal women to reduce the prevalence of hypertension and risk factors to avoid hypertension related cardiovascular death and other dare complications. University Heart Journal 2024; 20(1): 22-30